ANTESEDEN ADAPTIVE PERFORMANCE KARYAWAN GEN Z INDUSTRI PERBANKAN SWASTA DI JAKARTA SELATAN - Indrayani Nur Aini; Netania Emilisa; Aulia Rahma; Amanda Cantika Putri Efendhi; Nur Azhimarrofia (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The rapid digital transformation in recent years has changed the way people live and work, and has impacted businesses and organizations across every industry. In the private banking industry, Generation Z employees play a crucial role in ensuring service quality, operational accuracy, and smooth work processes. Therefore, it is crucial for every employee to strive to improve their adaptive capabilities. This study examines how Ethical Leadership and Despotic Leadership are influenced by Job Crafting in shaping Adaptive Performance. There were 150 responses to the survey. Instrumental tests such as validity and reliability, as well as hypothesis testing with SEM analysis using the AMOS program, were used to analyze this research. To ensure the validity and dependability of the instrument, this study examined the perceptions of Generation Z employees in private banks in South Jakarta. The findings indicate that Ethical Leadership and Job Crafting have a positive effect on Adaptive Performance, while Despotic Leadership has a negative effect. In addition, Job Crafting acts as a partial mediator in the relationship between Ethical Leadership and Adaptive Performance and as a full mediator in the relationship between Despotic Leadership and Adaptive Performance.